(untitled) (Bangladesh Journal of Agricultural Research, 2023)
Twelve gladiolus genotypes were collected and evaluated in the Research Field of Regional Agricultural Research Station, Akbarpur, Moulvibazar, during November 2018 to May 2020 for identifying suitable line(s) for commercial cultivation in north eastern region of Bangladesh. The genotype that produced flower stalk within minimum days of planting was GL-Akb-012 (66.16 days.The longest rachis length was recorded in GL-Akb-003 (80.12 cm) which was statistically significant from other eleven genotypes. Plant height varied considerably with the highest plant height in GL-Akb-012 (145.67 cm) and the lowest plant height was in GL-Akb-011 (89.33 cm). All of the genotypes in general, produced more than 12 florets per spike, however GL-Akb-001 produced the highest number of florets per spike (17.33). Vase life of the genotypes showed variation, GL-Akb-012 had the highest vase life of 9 days. The highest weight of corm found in GL-Akb-004 (320.00 g). In respect of variation in plants, for instance, flower quality, corm and cormel production characters, the gladiolus genotype GL-Akb-012 was most promising for commercial cultivation. Bangladesh J. Agril. Res. 46(3): 321-329, September 2021